Determinants of real exchange rate movements in 15 emerging market economies - Thomas Goda; Jan Priewe (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2019)
Previous work has established that an appreciation of the real exchange rate (REER) contributes to premature deindustrialization, less productive investment and dependence on commodity booms and busts in emerging markets economies (EME). From the previous literature, it is less clear however what the most important drivers for the cyclical REER movements in EME are. The main aim of this study is to provide empirical evidence about the determinants of the REER movements of 15 emerging markets during the last two decades, using statistical analysis and a dynamic panel fixed effects model approach. Our analysis shows that although "commodity" and "industrial" EME are heterogeneous, REER volatility tends to be higher among the former. Yet, REER volatility between emerging and advanced countries does not differ very much, apart from a few EME countries. Countries that had more stable REER trend fared better than those that had a depreciating or appreciating trend (with the notable exception of China). As theoretically expected, commodity prices are an important structural driver of REER movements in "commodity EME". Moreover, the results confirm the existence of the Harrod-Balassa-Samuelson effect, and show the importance of financial inflows. Further, exchange rate regimes and the intervention of central banks were partially successful to avoid more substantial appreciations (depreciations). Finally, we find that lower country risk and, at least in some periods, growing broad money has led to REER appreciations.
Keywords: F6; F31; F41; O11; O57; P52; 330; Real Exchange Rate; Foreign Exchange Rate Policy; Commodity Prices; CapitalInflows; Global Risk